MicroRNAs in Peripheral Mononuclear Cells as Potential Biomarkers in Hypertensive Patients With Heart Failure With Preserved Ejection Fraction. (1st March 2018) - Marketou, Maria E; Kontaraki, Joanna E; Maragkoudakis, Spyros; Patrianakos, Alexandros; Konstantinou, John; Nakou, Helen; Vougia, Despoina; Logakis, John; Chlouverakis, Gregory; Vardas, Panos E; Parthenakis, Fragiskos I
Abstract: BACKGROUND: MicroRNAs (miRs) regulate gene expression and play an important role in ventricular and vascular remodeling. However, there are limited data regarding their role in heart failure with preserved ejection fraction (HFpEF). The aim of this study was to assess gene expression of miR-1, miR-133a, miR-21, miR-208b, miR-499, and miR-26b in peripheral blood mononuclear cells (PBMCs) in hypertensive patients with HFpEF and to evaluate their association with their exercise capacity. METHODS: We included 56 hypertensive patients with HFpEF (age 67.29 ± 7.75 years). Forty-two hypertensive patients without HFpEF (age 66.83 ± 7.17 years) served as controls. All subjects underwent a cardiopulmonary exercise test (CPXT). PBMCs were isolated and levels of miRs were determined by quantitative real-time reverse transcription polymerase chain reaction. RESULTS: For hypertensive patients with HFpEF, higher expression levels in PBMCs were found only for miR-26b (7.6 ± 7.3 vs. 4.0 ± 3.6, P = 0.002), miR-208b (28.8 ± 35.3 vs. 7.5 ± 13.3, P < 0.001), and miR-499 (14.2 ± 22.4 versus 3.5 ± 2.9, P = 0.001). The strongest correlations with CPXT parameters were found for miR-208b levels, which had a positive correlation with maximal oxygen uptake (peakVO2 ) ( r = 0.671, P < 0.001), exercise duration ( r = 0.445, P = 0.001), and minute ventilation–carbon dioxide production relationship (VE/VCO2 ) ( r = 0.437, P = 0.001) in the HFpEF group. CONCLUSIONS: miR-26b, miR-208b, and miR-499 show a distinct in profile in hypertensive patients with HFpEF that is related with functional capacity. Further studies are needed to assess the role of miRs as prognostic tools or as therapeutic targets in those patients.